2004
DOI: 10.1248/bpb.27.617
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nitric Oxide and Tumor Necrosis Factor-.ALPHA. (TNF-.ALPHA.) Production by Propenone Compound through Blockade of Nuclear Factor (NF)-.KAPPA.B Activation in Cultured Murine Macrophages

Abstract: Lipopolysaccharide (LPS), which is a component of the cell walls of gram-negative bacteria, is one of the most potent macrophage activators. LPS induces the production of pro-inflammatory cytokines and small mediators, such as nitric oxide (NO) and PGE 2 in macrophages. Macrophage activation is known to play an important role in the inflammatory process.1) Increasing evidence also suggests that NO, a bioactive free radical, is involved in various pathophysiological processes including inflammation and septic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 18 publications
0
22
0
3
Order By: Relevance
“…Recent studies of natural products with anti-inflammatory activity have been reported, and many of them had been done using macrophage-like cell lines, RAW264.7 cells 8,10,16,[26][27][28] and THP-1 cells. 11,13) However, we chose human colon carcinoma cells for screening because we were focusing on anti-inflammatory compounds in dietary products which might be effective through the mucosal immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of natural products with anti-inflammatory activity have been reported, and many of them had been done using macrophage-like cell lines, RAW264.7 cells 8,10,16,[26][27][28] and THP-1 cells. 11,13) However, we chose human colon carcinoma cells for screening because we were focusing on anti-inflammatory compounds in dietary products which might be effective through the mucosal immune response.…”
Section: Discussionmentioning
confidence: 99%
“…15) Although the mechanisms of the anti-inflammatory effects of those materials are different, a wellknown mechanism has been described as inhibition of NF-B activation and NO production caused by antioxidant active compounds. 8,10,16) Buckwheat (Fagopyrum esculentum) is a health food in that it is rich in flavonoids such as rutin. 17) Rutin is an effective radical scavenger, 18) and Mukoda et al 19) have reported that buckwheat hull extract showed strong antioxidant activities in vitro and in vivo.…”
mentioning
confidence: 99%
“…2). LPS is known to induce NO production in macrophages (Lee et al 2004). It was suggested previously that NO may participate in the development of liver injury (Morikawa et al 1999).…”
Section: Bach1-deficiency Does Not Affect Lps-induced Tnf-α and No Prmentioning
confidence: 96%
“…FPP-3 (purity, >99%) used in this study was chemically synthesized in our group Lee et al, 2004). Bovine serum albumin, p-nitrophenol, thiobarbituric acid (TBA), 5,5′-dithiobis-2-nitrobenzoic acid, NADPH, glucose 6-phosphate, glucose 6-phosphate dehydrogenase, ethoxyresorufin, methoxyresorufin, pentoxyresorufin, benzyloxyresorufin, erythromycin, D,L-glyceraldehyde and corn oil were purchased from Sigma Chemical Co. (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%